The Effect of The Religious Learning Management Model on the Quality of Education Was Reviewed Based on Quantitative Analysis at SMA Negeri 5 Bandung - Misbahudin; Irawan; M. Sidiq Jaelani (Zona Education Indonesia, 2023)
The educational process involves the transformation of individual attitudes and behaviors, with the aim of nurturing and guiding the younger generation by imparting knowledge, values, and a fundamental outlook on life. Educational institutions implementing this process must understand the characteristics of effective schools and the framework for improving the quality of education. In terms of research methodology, quantitative data are used, which requires the collection of numerical data by the researcher. This data is obtained through variable measurements using research instruments. The collected data is then carried out statistical analysis. Based on the findings previously described, it can be concluded that learning management variables have a positive and significant effect on school quality. The manifestation of this phenomenon is seen on examination of the value of t, which yields a result of 3.668, exceeding the value of the table t by 1.658. Furthermore, an optimistic impact can be observed with a partial correlation coefficient of 0.311. This coefficient shows that learning management variables have a positive effect on school quality variables. In other words, with the improvement of the quality of learning management, the quality of schools also increases. Conversely, the quality of learning management decreases, as does the quality of schools. An R2 value of 0.898 provides further insight. This value illustrates that the variable of learning management contributes effectively by 89.8% to the quality of SMA Negeri 5 Bandung